Causes of Hospitalization in Systemic Lupus Erythematosus: A Narrative Review - da Rosa, Gilberto P.; Cervera, Ricard; Espinosa, Gerard (Current Rheumatology Reviews, 2021)
Hospitalizations are frequent in Systemic Lupus Erythematosus (SLE) and carry a significant economic burden. The focus of this review was to summarize the information available on the main causes of SLE hospitalizations over recent decades. A literature review was conducted, using PubMed and Scopus, for articles related to SLE hospital admissions from 1981 onward. Active disease/ flare and infection were the leading causes of admission across the study period. More recently, other comorbidities gained relevance, such as cardio and cerebrovascular disease, pregnancy-related morbidity, adverse drug reactions, thromboembolic events, malignancy and renal, pulmonary and gastrointestinal disease. African and Southeast Asian studies seemed to display particularly high percentages of patients admitted with active disease/flare, while European and North American studies appeared to report more admissions due to comorbidities and accumulated disease/treatment damage. Some data support a temporal change of certain admission causes, but the limited number, heterogeneity and variance among studies weakens a consistent analysis. In conclusion, despite the developments in SLE management, causes of hospitalization have not prominently changed across recent decades.
Keywords: hospitalization